Problems of the Independent Curriculum at State High School in Samarinda City - Annisa Istiqomah (UIN Sulthan Thaha Saifuddin Jambi, Pusat Kajian Kurikulum Pengembangan Pengajaran dan Pembelajaran (Center of Curriculum Studies, Teaching and Learning Development), 2024)
The Independent Curriculum has a program called the Driving School Program, the Driving School is the catalyst to realize the vision of Indonesia Education, a school that focuses on developing student learning outcomes holistically by realizing the Pancasila Student Profile, starting with superior Human Resources This research is included in the type of qualitative research with a descriptive approach. Initial socialization of the new curriculum was carried out to educators, students, and parents in the education unit. Educators will receive training from the ministry of education through IHT and PMM programs. Socialization to students and parents will explain the new curriculum system, changes in class majors, and improvement of the Pancasila Student Profile. Adjustments to new mindsets and methods are needed to understand curriculum changes. The school strives to develop the Operational Curriculum of the Education Unit (KOSP) and CP and TP to ensure meaningful and enjoyable learning. The learning tools involve teaching modules, project modules, and teaching materials according to the needs of students. Schools face obstacles in implementing the independent curriculum, ranging from the mindset to the readiness of schools, educators, students, and parents. The development of CP in each school is adjusted to the environment and the needs of students. The design of modules in the curriculum is more flexible but poses problems in its creation. The cost of implementing the project is also an issue, especially for schools with P5 projects and learning.